2018
DOI: 10.17576/jsm-2018-4706-01
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salinities on Gastric Emptying and Nutrient Absorption of Tiger Grouper × Giant Grouper (Epinephelus fuscoguttatus × E. lanceolatus) Hybrid

Abstract: The effects of salinity on the gastric emptying time (GET) and absorption of nutrient along the alimentary tract of tiger grouper (TG) × giant grouper (GG) (Epinephelus fuscoguttatus × E. lanceolatus) hybrid were studied. Juveniles TG×GG hybrid grouper (10.0 ± 0.5 cm total length; 50.5 ± 2.0 g) were reared in different salinities (10, 15, 20, 25 and 30 parts per thousand (ppt)) and fed with commercial pellet diet during the 60-day experimental period. The fish were then slaughtered sequentially at different t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…In sea bream ( Sparus aurata ) a 4‐ to 5‐fold increase in water absorption in the posterior intestine was observed when subjected at 55 ppt salinity (Gregorio et al., 2012). The gastric emptying was found to be highly salinity dependent and observed that at 25 and 30 ppt, longer time is needed to empty the digestive tract (Noor et al., 2018). There are few studies with freshwater fish that show the relationship between faeces and water salinity.…”
Section: Discussionmentioning
confidence: 99%
“…In sea bream ( Sparus aurata ) a 4‐ to 5‐fold increase in water absorption in the posterior intestine was observed when subjected at 55 ppt salinity (Gregorio et al., 2012). The gastric emptying was found to be highly salinity dependent and observed that at 25 and 30 ppt, longer time is needed to empty the digestive tract (Noor et al., 2018). There are few studies with freshwater fish that show the relationship between faeces and water salinity.…”
Section: Discussionmentioning
confidence: 99%
“…The fish were then deprived of food for 2 days and anesthetized with α-methyl quinoline FIGURE 1. Map depicting location of hatchery Pulau Ketam, Selangor, Malaysia (Transmore R ; Nika Trading, Puchong, Malaysia) (0.22 mL L -1 in 3 L of sea water as dan anasthetic medium for 10-15 min) (Das et al , 2014Noor et al 2018). The process of anaesthetization involved, first of all 3 L of sea water taken in a bowl and added 0.66 mg of α-methyl quinoline and stired vigorously for proper mixing.…”
Section: Sampling and Experimental Setupmentioning
confidence: 99%
“…Water temperature also influences the GE process of fish. Besides temperature, GE is also influenced by the following factors: size of food particles (the bigger the food particles the lower the GE), salinity (as salinity increases GE decreases), frequency of consumption (the higher the frequency of consumption the lower the GE), and dietary components (GE is faster in feed with fiber) [ 2 , 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…lanceolatus ) to other species. Epinephelus lanceolatus is challenging to breed and raise but introducing its superior genetic features into a hybrid allows for a faster growth rate in the hybrids [ 4 ]. The Sabah grouper is developed through the artificial combination of the Giant grouper milt and Tiger grouper eggs.…”
Section: Introductionmentioning
confidence: 99%